The impact of in utero tobacco exposure on smoking behaviors, cardiovascular disease risk and all-cause mortality in adulthood: A UK Biobank study - Yanxu Zheng; Xinyu Xiong; Jing Bao; Jingyu Liu; Jin Wang; Fang Zou; Zixi Chen; Yang Guo; Qingyao Wang; Yixuan Qiu; Zhaowei Zhu (Current Research in Toxicology)
The knowledge regarding the negative impacts of in utero tobacco exposure (IUTE) on cardiovascular disease (CVD) was incomplete. This study aims to assess the association between IUTE and the risks of CVD incidence and all-cause mortality, discuss the inter-group difference based on genetic susceptibility and smoking behaviors after birth, and explore the potential mediating factors. Utilizing a total of 375,024 participants from the UK Biobank, the outcomes include myocardial infarction, stroke, chronic ischemic heart disease, nonrheumatic aortic valve disorders, cardiomyopathy, heart failure, atherosclerosis, aortic aneurysm and dissection, and all-cause mortality. During a median follow-up period of 14.6 years, 50,434 cases of CVD were recorded. IUTE was significantly associated with increased CVD incidence (HR 1.10, 95 % CI 1.08–1.12) and all-cause mortality (HR 1.11, 95 % CI 1.09–1.14). Interaction effects between IUTE, smoking behaviors after birth, and genetic risk scores for CVD were observed significant (P for interaction < 0.005). The results of the cross-sectional study revealed a significant positive association between IUTE and smoking behaviors after birth (OR 1.08, 95 % CI 1.06–1.09). Mediation analysis indicated that smoking behaviors (Proportion = 12.40 %, P < 0.001) and HDL-c levels (Proportion = 14.20 %, P < 0.001) partially mediated the IUTE-CVD relationship. This study demonstrated that individuals with IUTE have a higher risk of developing CVD, and smoking behaviors after birth have multifaceted influence on this correlation. These findings underscore the importance of mothers avoiding smoking during pregnancy to mitigate adverse effects on their offspring.